Pengaruh Stabilitas Politik, Kriminalitas dan Daya Saing Global Terhadap Investasi Asing Langsung di 6 Negara Asean - Willa Novita Sari; Alpon Satrianto (Universitas Negeri Padang, 2021)
Study aims to determine the effect of political stability, crime and global competitiveness on foreign direct investment in 6 ASEAN countries by using secondary data from 2013 to 2019 and using panel data regresi analysis techniques. The results show that political stability has a positive and significant impact on foreign direct investment in 6 ASEAN countries. crime has a negative and significant effect on foreign direct investment in 6 ASEAN countries. Global competitiveness has a positive and insignificant effect on foreign direct investment in 6 ASEAN countries. And economic growth as a control variable has a positive and insignificant effect on foreign direct investment, foreign direct investment in 6 ASEAN countries. Together, political stability, crime, global competitiveness and economic growth affect foreign direct investment in foreign direct investment in 6 ASEAN countries.